The empirical review of the organizational, technological, environmental and human resources factors on the efficiency of the digital transformation, Oman / Nassr Khalfan Salim Al Maamari and Abul Bashar Bhuiyan - Salim Al Maamari, Nassr Khalfan; Bhuiyan, Abul Bashar (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
The Sultanate of Oman accepts and uses e-services among public services, which largely depend on the institutional process and implementation of e-government, sometimes with different preferences for the reality of digitalization. It is important and plays an important role in the economic, political and prosperity of the Middle East. Therefore, the country is focusing on technology that enables services and government-wide strategies. With these issues, the main aim of the study is to examine the means available to examine the effectiveness of electronic services and digital transformation in the selected public sector in the Sultanate of Oman. The study used online empirical sources in the names of organizational, technology, environment and human resource factors, as well as the effectiveness of digital change in various online database sources such as Google Scholars, Springer Link, Wiley, Science Direct, JSTOR, Emerald Full text, Scopus and EBSCO HOST, etc. The audit results show that organizational, technological, environmental and human factors play an important role in ensuring the effectiveness of the public sector in the digital transformation in the Sultanate of Oman. The study also found that the success of e-government in Oman depends on the willingness and intention of citizens to use the e-government services. The country's government should consider developing vital IT projects, ignoring citizens' opinions, to make traditional services more efficient online. Understanding citizen adoption is an important element of E-Government, enabling it to provide policymakers and decision makers with a range of strategic management plans and actions to build and rapidly accelerate adoption of these services to increase citizen participation, also the adoption rate. A summary of the study's findings provides guidance for the future scope of empirical research to ensure the effectiveness of the public sector for digital change in the Sultanate of Oman and its regions.